INTEGRATION OF BLIND ADOLESCENTS INTO HIGHER EDUCATION (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article provides information on the problems of integrating adolescents with visual impairments into higher education, the introduction of inclusive education and the use of inclusive education in Higher Education in Uzbekistan and foreign countries, the education of children with disabilities among healthy children and the conditions created for them. The article also cites modern technologies and techniques that can be used to educate blind adolescents.